FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ROKOK ELEKTRIK (VAPE) PADA MAHASISWA INSTITUT TEKNOLOGI DAN BISNIS INDRAGIRI - Monifa Putri; Fitriyani Bahriyah (Universitas Batam, 2023)
Cigarettes are common and a health problem in the world. The habit of smoking is like a culture in Indonesia. Not only parents, teenagers and children also have smoking behavior and habits. In Indonesia, conventional cigarettes are no stranger to society, now a new trend has emerged, namely the use of electric cigarettes or vapes. Therefore it is necessary to know the factors that influence the use of electric cigarettes (vape) among students of the Indragiri Institute of Technology and Business. The research method used is analytic with a cross sectional approach. The results showed that out of 96 students, 9,4% used electric cigarettes (vape). The results of the chi square test for family environmental factors obtained a p value of 0.00, p value of 0.00 for lifestyle factors and p value of 0.00 for social environmental factors. The conclusion from this study is that there is an influence between family environmental factors, lifestyle and social environment with the use of electric cigarettes (vape) in students of the Indragiri Institute of Technology and Business.